1984
DOI: 10.1111/j.2042-3306.1984.tb01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle perfusion in the horse

Abstract: Summary Muscle perfusion was studied in conscious and anaesthetised horses by monitoring the clearance of a locally injected bolus of saline containing radioactive xenon (133Xe). The mean of all the measurements made from the brachiocephalicus and semimembranosus muscles in conscious subjects was 1.29 ml/min/100 g while in anaesthetised subjects it was 0.40 ml/min/100 g. The significance of these results is discussed in relation to the clinical occurrence of post anaesthetic myositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 11 publications
0
21
1
Order By: Relevance
“…1998b; Raisis et al. 2000), 133 Xe clearance (Weaver & Lunn 1984) and microspheres (Manohar et al. 1987; Goetz et al.…”
Section: Introductionmentioning
confidence: 99%
“…1998b; Raisis et al. 2000), 133 Xe clearance (Weaver & Lunn 1984) and microspheres (Manohar et al. 1987; Goetz et al.…”
Section: Introductionmentioning
confidence: 99%
“…Anaesthesia‐related decreases in skeletal muscle blood flow are readily quantified. The first study published in this area used radioactive xenon 133 clearance to compare microvascular perfusion in the pelvic limb muscles of conscious and halothane‐anaesthetized horses (Weaver et al. 1984) and demonstrated that perfusion decreased markedly during anaesthesia.…”
Section: Inhalation Agentsmentioning
confidence: 99%
“…Radioactive xenon 133 clearance was one of the first techniques used to non‐invasively record microvascular perfusion in conscious and anaesthetized horses (Weaver et al. 1984).…”
Section: Radioactive Xenon Clearancementioning
confidence: 99%
“…1984). This technique calculates microvascular blood flow from the rate of clearance of a small volume (0.2 mL) of radioactive xenon 133 injected at an intramuscular site (Weaver et al. 1984).…”
Section: Radioactive Xenon Clearancementioning
confidence: 99%